DESIGN AND ANALYSIS OF PPM BASED VISIBLE LIGHT COMMUNICATION SYSTEM WITH DIMMING SUPPORT - Latif, Alina; Sohail, Muhammad (MATTER: International Journal of Science and Technology, 2017)
Visible light communication (VLC) is a green technology which is the replacement of the existing conventional radio frequency based indoor communication system. VLC system fundamentally comprises of a light source such as high brightness light emitting diodes (HBLEDs) that can accomplish dual function simultaneously i.e., illumination as well as data transmission. This paper presents a circuit design and analysis of PPM based VLC system and demonstrates the dimming control scheme. In this regard, front ends of the transmitter and the receiver were tested successfully by sending and consequently receiving equal width PPM frame via MATLAB. As it is known that dimming is an essential part of illumination and traditionally it is achieved by using pulse width modulation (PWM). Compared to PWM, PPM is facile to be applied since constant illumination level is easily achieved by PPM irrespective of data bits. The results show that either bits are (0000) or (1111) the illumination remained same i.e., 50% illumination level. Moreover, the VLC system with dimming support was tested for communication having 2m range.